Effects of different heat processing methods of rapeseed on ruminal and post-ruminal nutrient disappearance - Paya, H; Taghizadeh, A; Hosseinkhani, A; Mohammadzadeh, H; Janmohammadi, H; Moghaddam, G (Journal of the Hellenic Veterinary Medical Society, 2022)
Due to improving the nutritive value of oilseeds and changing their digestion site in ruminants, processing, including heat treatment, seems necessary. The present research was conducted to evaluate the effect of applying heat processing such as roasting, microwaving and autoclaving on nutritive values; the amount and rate of degradability in rumen, and the disappearance of rapeseed nutrients in rumen, post-rumen and total tract. This evaluation was performed using mobile nylon bags techniques; three-step method of digestion and protein CNCPS fraction. A completely randomized design was used to investigate the effect of applying heat processing, and SAS software was used to analyze the data. The field Emission Scanning Electron Microscope was used to monitored the effect of heat treatment on surface of rapeseed. The application of heat processing in this research (roasting, microwaving and autoclaving) had no significant effect on the chemical composition of rapeseed. The results obtained from mobile nylon bags method and three-step digestion method showed that raw rapeseed has the highest disappearance of DM and CP in rumen and therefore has a significant difference with processed seeds (P<0.05). Also, the disappearance of DM and CP of processed rapeseed in intestines was significantly higher than raw seed (P<0.05), and this was higher than other processing for autoclaved rapeseed. According to the results obtained from CNCPS protein fractionation, applying heat processing altering protein fractionation (P<0.05). Applying microwave processing has created cracks in the surface of the rapeseed wall, and this condition was not observed in the wall surface of other heated seeds. In general, it can be said that in addition to increasing the digestibility of rapeseed in the entire gastrointestinal tract, applying heat processing reduces its degradability in the rumen and has increased the disappearance of nutrients in the intestine, that it can be stated the digestion site is altered from rumen to intestine, which can prevent the loss of protein sources in ruminant feed.